Quantification and toxicity testing of pharmaceuticals in tropical marine sediments, All Saints Bay, Bahia, Brazil - Beretta, Magda (2013)
The presence and effects of pharmaceuticals in the environment have gained increased attention lately because of their widespread use and their potential to bioaccumulate and induce negative effects in aquatic and terrestrial ecosystems. This work presents the quantification of pharmaceutical compounds in sediments of All Saints Bay, Bahia, Brazil and toxicity testing of the compounds Atenolol, Erythromycin and Caffeine on sediment microorganisms and microcrustaceans (Artemia salina). Pharmaceuticals were shown to be widely distributed in sediments of All Saints Bay, in areas near the capital Salvador as well as in more remote areas of the bay. Toxicity tests revealed a susceptibility of microorganisms and microcrustaceans to both Erythromycin and Caffeine at higher concentrations, while Atenolol did not cause toxic effects. The presence of pharmaceuticals at the levels detected did not imply acute toxicity to microorganisms and microcrustaceans.